2020
DOI: 10.3390/cancers12103032
|View full text |Cite
|
Sign up to set email alerts
|

Completion Total Thyroidectomy Is Not Necessary for Papillary Thyroid Microcarcinoma with Occult Central Lymph Node Metastasis: A Long-Term Serial Follow-Up

Abstract: The necessity of completion total thyroidectomy in patients with papillary thyroid microcarcinoma (PTMC) and pathological central lymph node metastasis (pCLNM) who underwent thyroid lobectomy with central compartment neck dissection (CCND) is unclear. We determined the necessity of completion total thyroidectomy by retrospectively comparing the prognosis according to the presence of pCLNM during a long-term follow-up. We enrolled 876 patients with PTMC who underwent thyroid lobectomy with prophylactic CCND fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…LN metastasis, one of the criteria for categorizing DTC as ATA intermediate risk, is very common in patients with DTC and is observed in up to 80% of cases (28,29). It remains controversial whether occult LN micrometastasis is associated with recurrence, although it is not associated with disease-specific mortality (30)(31)(32). Our study showed that LN micrometastasis was not associated with the recurrence rate.…”
Section: Discussionmentioning
confidence: 49%
“…LN metastasis, one of the criteria for categorizing DTC as ATA intermediate risk, is very common in patients with DTC and is observed in up to 80% of cases (28,29). It remains controversial whether occult LN micrometastasis is associated with recurrence, although it is not associated with disease-specific mortality (30)(31)(32). Our study showed that LN micrometastasis was not associated with the recurrence rate.…”
Section: Discussionmentioning
confidence: 49%
“…Te median follow-up is 12.8 ± 4.3 (8.3-30.5) years and 13.4 ± 4.4 (8.3-32.3) years, respectively. According to these results, the authors concluded that the second total thyroidectomy surgery is not necessary in patients with positive CLN metastasis after the pCND [33]. Terefore, when the number of microscopic metastatic lymph nodes >5, patients can choose a second total thyroidectomy or an active surveillance strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Papillary thyroid carcinoma (PTC) was the most frequent histological subtype of thyroid malignancy which has a rapidly rising incidence worldwide in the last few decades (1,2). In total, 20.7-62% of patients with PTC present cervical lymph node metastasis (LNM) at initial diagnosis, which was associated with a poor prognosis (3,4), yet the recently updated 8th edition of the TNM staging system eliminates the difference between central (N1a) and lateral (N1b) LNM, and N1b disease is not adopted for the final staging classification (5)(6)(7). These changes have been questioned, and concern arises in such a way that ignoring the metastatic lymph node sites may underestimate recurrence and mortality in patients with PTC.…”
Section: Introductionmentioning
confidence: 99%